Mechanical Behavior of Ceramic Monolithic Systems With Different Thicknesses - Longhini, D. [UNESP]; Rocha, C. O. M. [UNESP]; Oliveira, L. T. de [UNESP]; Olenscki, N. G. [UNESP]; Bonfante, E. A.; Adabo, G. L. [UNESP] (Operative Dentistry Inc, 2019)
Objectives: This study assessed the fully stabilized zirconia (FSZ) Prettau Anterior, the partially stabilized zirconia (PSZ) Prettau, and the lithium disilicate IPS e.max CAD (LD) through microstructural and mechanical characterization and effect of thickness on fracture load of the ceramics. Methods and Materials: Disk-shaped specimens (12 mm diameter and 1.2 mm thickness) were prepared for biaxial flexural strength (BFS) and Weibull statistics (n=30). For the fracture load static test (FLST) and Weibull statistics (n=30), disk-shaped specimens 12 mm in diameter and thicknesses of 0.5 mm, 1 mm, and 1.5 mm were cemented on an epoxy-resin substrate. Results: BFS (MPa) results were PSZ: 683.0 +/- 70.23; FSZ: 438.6 +/- 64.1; and LD: 248.6 +/- 37.3. One-way analysis of variance (ANOVA) for BFS was significant (p<0.001), and the Tukey post hoc test showed differences among all ceramics. There was difference in characteristic strength, but there was no difference in Weibull modulus. Two-way ANOVA for FLST was significant for ceramic (p<0001), thickness (p<0001), and interaction (p<0001). There was no difference among all ceramics at the 0.5 mm thickness. PSZ had higher values for the 1.0 mm and 1.5 mm thicknesses. LD of 1.5 mm thickness exhibited a higher FLST than FSZ. Conclusions: PSZ had the highest BFS, but when cemented on a substrate, all ceramics with 0.5 mm thickness behaved similarly. Despite the lower BFS, LD had a fracture load similar or superior to FSZ when cemented on a substrate.